# Calculator search results

Formula
Solve the equation
Graph
$y = x - \left ( 2 x + 1 \right )$
$y = 8 - \left ( 3 x + 3 \right )$
$x$Intercept
$\left ( - 1 , 0 \right )$
$y$Intercept
$\left ( 0 , - 1 \right )$
$x$Intercept
$\left ( \dfrac { 5 } { 3 } , 0 \right )$
$y$Intercept
$\left ( 0 , 5 \right )$
$x- \left( 2x+1 \right) = 8- \left( 3x+3 \right)$
$x = 3$
 Solve a solution to $x$
$\color{#FF6800}{ x } \color{#FF6800}{ - } \left ( \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \right ) = \color{#FF6800}{ 8 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right )$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } = \color{#FF6800}{ 5 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x }$
$- x - 1 = \color{#FF6800}{ 5 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x }$
 Organize the expression 
$- x - 1 = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 }$
$\color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 1 } = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 5 }$
 Organize the expression 
$\color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ 5 } \color{#FF6800}{ + } \color{#FF6800}{ 1 }$
$\color{#FF6800}{ - } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 5 + 1$
 Organize the expression 
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } = 5 + 1$
$2 x = \color{#FF6800}{ 5 } \color{#FF6800}{ + } \color{#FF6800}{ 1 }$
 Add $5$ and $1$
$2 x = \color{#FF6800}{ 6 }$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } = \color{#FF6800}{ 6 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \color{#FF6800}{ 3 }$
 그래프 보기 
Graph
Solution search results